The New Brutalism: Ethic vs. Marxism? Ideological Collisions in Post-War English Architecture - Groaz, Silvia (Histories of Postwar Architecture, 2020)
At the end of the Second World War, an intense ideological confrontation took place in England, where the principles of reconstruction were established around the ‘low rise’ and ‘high rise’ dichotomy. The debate was influenced by a politicized generational divide, pitting the legacy of Howard’s Garden City model, supported by those who called themselves ‘Marxists’, against Le Corbusier’s Unité at Marseille, defended by a younger generation of architects who took a ‘non-Marxist’ position. The various political tendencies were translated into stylistic rules that addressed types, city configuration, and even materials, according to a rich constellation of new labels: the New Humanism derived from Soviet Social Realism, the William Morris Revival and People’s Detailing, the New Picturesque advocated as a democratic model by Nikolaus Pevsner, and the New Empiricism reworked by Eric de Maré on the Cooperative Housing Schemes of the Swedish welfare state. It is in this context that the New Brutalism originated. The term disguised subversive attributes with respect to the relationship of urban and architectural models with political demands. The rigid ideological instances that configured a conventional model for the reconstruction were purged in the New Brutalism through the introduction of a category that supplanted Marxist ideology. Ethics, translated into the truth to materials and structure, as well as into the concept of ‘as found’, paved its way through an argument rooted in the architectural discourse.